"This is fake news": Investigating the role of conformity to other users' views when commenting on and spreading disinformation in social media. (August 2019) - Colliander, Jonas
Abstract: This study examines the effects of conformity to others online when individuals respond to fake news. It finds that after exposure to others' comments critical of a fake news article, individuals' attitudes, propensity to make positive comments and intentions to share the fake news were lower than after exposure to others' comments supportive of a fake news article. Furthermore, this research finds that the use of a disclaimer from a social media company alerting individuals to the fact that the news might be fake does not lower individuals' attitudes, propensity to make positive comments and intentions to share the fake news as much as critical comments from other users. Highlights: Fake news is an increasing problem online. Tests whether users conform to others' Facebook comments of fake news. Also tests whether others' comments were more important than 'fake flags'. Others comments significantly affected attitudes and intentions to share. Social media companies should stimulate debunking by other users.